Extent of Team Cohesion Affecting the Student Athlete Well-Being in a Technology University in Hubei, China (Journal of Interdisciplinary Insights, 2024)
Team cohesion is a fundamental component of sports success, playing a crucial role in shaping team dynamics, enhancing individual performance, and supporting the overall well-being of athletes. This study explores the extent of team cohesion and its impact on the well-being of student-athletes at Hubei University of Automotive Technology, China. The research investigates how student-athletes perceive team cohesion in terms of task cohesion, social cohesion, and leadership, and evaluates their physical, mental, and emotional well-being. Using a descriptive-correlational design, data were collected from 150 student-athletes through a structured questionnaire. The results indicated high levels of team cohesion, with significant differences in task cohesion based on athletic experience, though no gender differences were observed. Athletes reported strong well-being, particularly in emotional and physical dimensions. The study suggests early team-building activities, leadership development programs, and enhanced mental health support as effective strategies to strengthen team cohesion and well-being. This research highlights the importance of cohesive team dynamics in fostering both athletic performance and holistic well-being among student-athletes.